Anomalous transport and magnetic properties induced by slight Cu valence alternation in layered oxytelluride BiCuTeO. Issue 32 (18th May 2020) - Luo, Ye-Cheng; Lin, Dajun; Zhang, Yan-Yan; Dong, Song-Tao; Yao, Shu-Hua; Lv, Yang-Yang; Zhou, Jian; Chen, Y. B.
Abstract : A nonlinear Hall effect and weak antiferromagnetism are induced by mixed-valence Cu in BiCuTeO. Abstract : In this paper, we report on the transport and magnetic properties of layered oxytelluride BiCuTeO polycrystals with slight mixed valence of Cu. The temperature-dependent electrical resistivity reveals degenerate semiconductor behavior (similar to metals). Under the action of an external magnetic field, the BiCuTeO polycrystal sample exhibits unsaturated magnetic resistance (MR) of about 8% at 2 K and 9 Tesla. The Hall resistivities show nonlinear behavior, suggesting the coexistence of both electrons and holes in the sample. When the temperature is decreased to around 110 K, the dominant carriers are changed from electrons to holes from the viewpoint of electrical transport, which is supported by the calculated temperature-dependent Fermi energy. Meanwhile, at low temperatures (<100 K), the impurity magnetic moment formed by a small amount of positive divalent copper exhibits short-range magnetism (a spin-glass-like feature), which gives rise to a narrow magnetic hysteresis loop. Our work may benefit in-depth understanding of physical properties of BiCuTeO-based materials.